Productivity of Spring Wheat Using Megamix Mineral Fertilizers - Vasin Vasily; Burunov Alexey; Vasina Natalia; Strizhakov Anatoly (BIO Web of Conferences, 2021)
The paper shows the research results related to the development of methods to increase the yield of spring wheat using Megamix liquid mineral fertilizers in the presowing treatment of seeds, treatment of crops on vegetation when introducing mineral fertilizers in seedbed preparation in the forest-steppe conditions of the Middle Volga region. The studies were carried out on the experimental field of Samara State University in 2017-2020. During the three-factor field experiment, dry matter accumulation and photosynthetic activity were evaluated with the analysis of photosynthetic potential and net productivity of photosynthesis. It was established that the best indicators are formed on versions with the treatment of seeding material with Megamix Seeds or Megamix Profi agents with subsequent double treatment on vegetation with Megamix Profi in the amount of 0.5l/ha (in the tillering phase) + Megamix Nitrogen in the amount of 0.5l/ha (in the flag leaf phase) against the background of N32P32K32 fertilizer application. The application of Megamix agents in the system of seed treatment + treatment of crops with Megamix stimulating agents provides the maximum accumulation of dry matter in the version of Megamix Seeds treatment and the treatment of crops with a mixture of Megamix Profi + Megamix Nitrogen – 591.9 g/m on soft crops and 622.6 g/m2 – durum wheat against the background of N32P32K32 application. The maximum photosynthetic potential of 0.968…1.091 million m2/ha per day is formed in these versions, and, consequently, the maximum yields with values of 3.73 t/ha on soft wheat crops and 3.44 t/ha on durum wheat crops. It was found that the use of liquid mineral fertilizers on all versions of the experiment reliably increases the yield of spring wheat.